Quatre géographes face à leurs émotions - Véronique André-Lamat; Marie Faulon; Etienne Jacquemet; Isabelle Sacareau (Carnets de Géographes, 2016)
Within the context of the April 25, 2015 Nepal earthquake, this paper examines how four researchers deal with the disaster throught the lens of their emotions whether they are on site or away. Their personnal accounts show that their localisation both in Nepal and in France does not interfere much in the nature and the organisation of emotions. Those are indeed almost the same. Aside from an extra-ordinary event, the mechanisms which originally produce emotions and their differential impact on individuals, are widely based on various and personal references related to the researchers past experiences, fieldwork, careers and status. Finally, these emotions are also channeled more or less strongly according to each person’s capacity to act and adapt him or herself to space and distance.